Cortical adrenocarcinoma, a rare cause of abdominal pain - Ospino-Guerra, María Clara (2023)
Cortical adrenocarcinoma is a rare neoplastic pathology with poor prognosis. It produces hormone hypersecretion, causing fortuitous clinical and disparate findings. We present the case of a 32-year-old female patient admitted to the emergency department for abdominal pain, weight loss and palpable mass. Imaging showed a large heterogeneous mass, dependent on the right adrenal gland, in addition to hypercortisolism not dependent on ACTH. She was treated with surgical resection, radiotherapy and mitotane, evolving positively. An infrequent cause of abdominal pain is evidenced in which clinical suspicion, paraclinical support and imaging findings allowed the optimal diagnostic and therapeutic approach.